Desain Kemasan Susu Segar dalam Upaya Peningkatan Daya Beli Di Desa Mekar Sari - Saputra, Aditia; Saputra, Peni; Sahputra, Ikwan; Azhari, Diah; Khairil, Khairil; Nur’aini, Hesti; Fariadi, Herri (Universitas Dehasen Bengkulu, 2025)
This community service activity focuses on packaging design for dairy products in Mekar Sari Village as a strategy to increase the selling value and competitiveness of local products. The main problem faced is the lack of brand identity and attractive packaging, which makes it difficult for products to compete in the market. Methods The service activity uses an observational approach and data triangulation through direct observation, informal interviews, and documentation. The result is the development of a packaging design that reflects the professionalism, freshness, and quality of the product, including the use of logos, modern visual design, and bilingual information. The campaign not only increased brand awareness but also provided training to the community on branding and marketing. Further recommendations include the use of eco-friendly packaging materials and storytelling on the packaging to create an emotional attachment with consumers.